Pengaruh Terapi Mirror Therapy dan Motivasi Pasien terhadap Kemampuan Motorik Tangan pada Pasien Hemiparese di Puskesmas Ci Herang Tahun 2025 - Muhammad Rafi Mahesa; Weslei Daeli; Rina Afrina (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Stroke often causes hemiparesis, which impairs hand motor skills and independence in daily activities. Mirror therapy is a rehabilitation intervention that stimulates motor function through visual feedback, while patient motivation plays a crucial role in exercise adherence. This study aims to analyze the effect of mirror therapy and patient motivation on hand motor skills in patients with hemiparesis.The study used a quasi-experimental design with a pretest–posttest approach in 30 hemiparesis patients undergoing rehabilitation at the Ciherang Community Health Center. Mirror therapy intervention was administered for 20–30 minutes, three times per week for four weeks. Hand motor skills were measured using Manual Muscle Testing on a scale of 0–5, while patient motivation was assessed using a questionnaire.The results showed a significant increase in hand motor skills after mirror therapy (p < 0.05) and higher patient motivation was associated with greater motor score improvement (p < 0.05). Mirror therapy and patient motivation have been shown to have a positive effect on hand motor skills in hemiparesis patients, so this combined intervention can be considered as part of a stroke rehabilitation program.